Association between race and receipt of counselling or medication for smoking cessation in primary care. (14th October 2017) - Hooks-Anderson, Denise R; Salas, Joanne; Secrest, Scott; Skiöld-Hanlin, Sarah; Scherrer, Jeffrey F
Abstract: Background: Previous evidence of race disparities in smoking cessation treatment has been limited to mostly survey studies which increase the potential for recall bias. We examined if African American versus white patients in primary care are less likely to receive any treatment or if race disparities are specific to the type of treatment offered using data pulled from a large electronic health record system. Methods: Medical record data from 3510 white and 2707 African American patients were available from primary care encounters between 2008 and 2015 and was used to define smoking status, cessation treatments (counselling and medication), and covariates. The association between race and type of smoking cessation treatment offered was measured by logistic regression models before and after adjusting for covariates. Results: Smoking cessation counselling was offered to 9.3% of African American and 7.8% of white patients, and a prescription for smoking cessation medication was offered to 12.3% of African American and 16.4% of white patients. After adjusting for covariates in logistic regression models, whites were significantly less likely than African American patients to receive smoking cessation counselling [odds ratio (OR) = 0.81; 95% confidence interval (CI) = 0.65–0.99] and were significantly more likely to receive a prescription for a smoking cessation medication (OR = 1.23; 95% CI = 1.03–1.47). Conclusions: Less than 20% of smokers received any type of therapy to assist in smoking cessation. We observed a race disparity in type of smoking cessation therapy provided to white and African American primary care patients. Further research is needed to increase treatment rates and eliminate disparities.